Functional analysis of the UVR8 photoreceptor from the monocotyledonous Zea mays - Fernández, María Belén (2020)
Low UV-B fluence is a signaling stimulus that regulates various physiological processes and induces photomorphogenic responses in plants. The specific UV-B receptor UVR8 is a key component in these processes. Although UVR8 sequence is conserved, few homologs have been cloned and reported to be functional. Here we show the cloning and functional analysis of Zea mays UVR8 (ZmUVR8). ZmUVR8 presents 73% of identity with AtUVR8, maintaining the key tryptophan responsible of UV-B perception. ZmUVR8 also contains the VP domain, involved in the interaction with the proteins CONSTITUTIVELY PHOTOMORPHOGENIC 1 (COP1) and REPRESSOR OF UV-B PHOTOMORPHOGENESIS 1 (RUP1). Whereas UVR8 was expressed in non-irradiated Arabidopsis and maize leaves, after 2 h of UV-B irradiation, its expression was reduced. The expression of chalcone synthase (CHS), involved in flavonoid biosynthesis and regulated by UVR8, was increased in irradiated Arabidopsis and maize leaves. Arabidopsis uvr8-1 null mutant was complemented with ZmUVR8 driven by the CaMV-35S promoter and fused to eGFP. ZmUVR8-eGFP fusion was mainly localized in nuclei of transgenic lines, irrespective of UV-B treatments. UV-B suppressed hypocotyl elongation in wild type (WT) Arabidopsis plants, whereas in uvr8-1 hypocotyl growth was observed. However, hypocotyl elongation was reduced in UV-B irradiated transgenic lines complemented with ZmUVR8. Moreover, CHS and transcription factor HY5 (ELONGATED HYPOCOTYL 5) expression were also restored in these plants. These results confirm that ZmUVR8 is similar enough to AtUVR8 to restore UV-B perception and signaling in Arabidopsis mutant uvr8-1, thus being a functional UV-B photoreceptor. That reinforce the importance of UVR8 as a functional UV-B-responsive regulator in land plants.